Pandemia: Academic Lives and COVID-19, Before, During, and Whenever After - Watermeyer, Richard (International Higher Education, 2022)
For academics the world over, the COVID-19 pandemic has been, and remains, a source of profound and enduring disruption. Yet arguably its greatest disruptive influence has been to exacerbate, and thus force a reckoning of, the deep-seated problems that have for some time caused academics to question their future. This article presents survey findings drawn from academics in four country settings and reflections on the deteriorating state of academic life under COVID.